Les émotions au service de la métamorphose identitaire des professeurs stagiaires d’anglais de l’académie de Créteil - Marie-Claire Lemarchand-Chauvin (Recherches en Éducation)
Pre-service teachers undergo many emotional episodes (LeMarchand-Chauvin & Tardieu, 2018) during the year of their initial training, and their “in-between” position – half-student and half-teacher – can make it even more painful and difficult to cope with. During this transitional period, which could be compared to adolescence, pre-service teachers’ professional identity is gradually going to develop and emerge. This research was conducted with two cohorts of pre-service English teachers from the academy of Créteil (France). It is based on the hypothesis that their metamorphosis process could be sustained through the sharing their emotions (Rimé, 2005) with their peers in support groups, sessions of analysis of professional practice (Clos, 1999; Etienne & Fumat, 2014) based on empathic listening, and through body and voice expression workshops (Pujade-Renaud, 1984; Tellier & Cadet, 2014). Setting emotions and empathy at the core of pre-service teachers’ training could give novice teachers access to reflectivity (Schön, 1983, 1987), to professional growth or metamorphosis.